EFEKTIVITAS BPJS DALAM PERSPEKTIF PENINGKATAN PELAYANAN JAMINAN KESEHATAN NASIONAL DI SELEMADEG TIMUR II KABUPATEN TABANAN - Swicahyani, Ni Gusti Ayu Kadek Devi; Wijaya, Komang Adi Sastra; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 2 No 2 (2022): Administrasi Publik 2022, 2023)
Minister of Health Regulation 43 of 2019 concerning Health Center states that Puskesmas are Health Service Facilities. The Selemadeg Timur II Health Center has berseni mission to provide proper health services in accordance with Law no. 24 of 2014 concerning National Health Insurance. The Social Security Administering Body (BPJS) for Health is an Indonesian StateOwned Enterprise (BUMN) specially assigned by the Government of Indonesia to administer berseni national social security system for all Indonesian citizens. According to Law no. 24 of 2011 BPJS is berseni public legal entity that was formed to carry out insurance programs, especially health insurance. Based on the background of this research, the aim is to determine the effectiveness of BPJS in the perspective of improving the National Health Insurance service in Selemadeg Timur II. Keywords: Program Effectiveness, BPJS Health, National health insurance